Facilitators and Barriers to Implementing Clinical Governance: A Qualitative Study among Senior Managers in Iran - RAVAGHI, Hamid (Iran J Public Health, 2014)
BACKGROUND: Health care systems should assign quality improvement as their main mission. Clinical governance (CG) is a key strategy to improve quality of health care services. The Iranian Ministry of Health and Medical Education (MOHME) has promoted CG as a framework for safeguarding quality and safety in all hospitals since 2009. The purpose of this study was to explore perceived facilitators and barriers to implementing CG by deputies for curative affairs of Iranian medical universities. METHODS: A qualitative study was conducted using face to face interviews with a purposeful sample of 43 deputies for curative affairs of Iranian Medical Universities and documents review. Thematic analysis was used to analyze the data RESULTS: Five themes were explored including: knowledge and attitude toward CG, culture, organizational factors, managerial factors and barriers. The main perceived facilitating factors were adequate knowledge and positive attitude toward CG, supporting culture, managers’ commitment, effective communication and well designed incentives. Pe rceived barriers were the reverse of facilitators noted above in addition to insufficient resources, legal challenges, workload and parallel quality programs. CONCLUSIONS: Successful implementation of CG in Iran will require identifying barriers and challenges existing in the way of CG implementation and try to mitigate them by using appropriate facilitators.